2011
DOI: 10.15669/pnst.2.421
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Impurity Activation in the RBMK Reactor Graphite Using MCNPX

Abstract: Numerical modelling is an important tool for estimation of the radioactive waste generation at the nuclear energy sites. In this work we have applied a Monte Carlo code, MCNPX version 2.6 for calculation of activation of the graphite stack in the RBMK-1500 reactor. The simplified 3D model of the RBMK-1500 reactor core fragment with 14 fuel assemblies and 2 control rods distributed according to the real RBMK-1500 reactor core geometry has been created.Use of the Monte Carlo method for estimation of impurity act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…[8] In order to acquire an accurate and cost-effective radiological characterization of a large number of specimens, neutron activation models can be developed on the basis of available information about material and structural composition, together with irradiation history of the samples. [9,10] At this aim, elemental composition of the impurities present in virgin graphite must be determined, as they are neutron activation precursors. However, historical nuclear grades are often no longer available and very few complete elemental characterization studies of non-irradiated samples have been carried out, especially for what concerns light and volatile elements such as Li, B, N and Cl, which are important precursors of medium ( 3 H) and long living ( 14 C and 36 Cl) neutron activation radionuclides.…”
Section: Methodsmentioning
confidence: 99%
“…[8] In order to acquire an accurate and cost-effective radiological characterization of a large number of specimens, neutron activation models can be developed on the basis of available information about material and structural composition, together with irradiation history of the samples. [9,10] At this aim, elemental composition of the impurities present in virgin graphite must be determined, as they are neutron activation precursors. However, historical nuclear grades are often no longer available and very few complete elemental characterization studies of non-irradiated samples have been carried out, especially for what concerns light and volatile elements such as Li, B, N and Cl, which are important precursors of medium ( 3 H) and long living ( 14 C and 36 Cl) neutron activation radionuclides.…”
Section: Methodsmentioning
confidence: 99%
“…Monte Carlo based codes have been widely recommended and exploited to simulate neutron activation of nuclear reactors components [17] [26] [18]. In this work, MCNP6…”
Section: Simulation Of Activation By Mcnpmentioning
confidence: 99%
“…In order to support the radiological characterization of L-54 M moderator and reflector graphite, a neutronic model of the reactor has already been developed by MCNP (Monte Carl N-Particle) [7] [14] [15] [16]. This probabilistic Monte Carlo code was chosen for the simulation considering its well documented capabilities for this task, as it can be found in the literature [17] [18]. Furthermore, this computational approach is recommended for the radiological characterization of radioactive matrices, when neutron activation prevails on contamination [17].…”
Section: Introductionmentioning
confidence: 99%
“…To characterize the radioactive waste the experimentally validated model was developed for simulation of radiological characteristics of different parts of nuclear reactor during operation and decommissioning periods (Plukiene et al 2011) using experimentally obtained graphite impurity concentrations and the available data from the scientific literature, which is limited for this specific sort of nuclear graphite (Ancius et al 2005; Puzas et al 2010). As the calculation of neutron activation graphite structures has revealed that the principal uncertainty of induced activity is due to a high variation of impurity concentrations in nuclear graphite, it is extremely important to determine the impurity concentration in several samples from different graphite construction parts (Plukiene et al 2014).…”
Section: Introductionmentioning
confidence: 99%